A Theranostic Cellulose Nanocrystal‐Based Drug Delivery System with Enhanced Retention in Pulmonary Metastasis of Melanoma - Imlimthan, Surachet; Khng, You Cheng; Keinänen, Outi; Zhang, Wenzhong; Airaksinen, Anu J.; Kostiainen, Mauri A.; Zeglis, Brian M.; Santos, Hélder A.; Sarparanta, Mirkka (Small (Weinheim an der Bergstrasse, Germany), 2021)
Metastatic melanoma can be difficult to detect until at the advanced state that decreases the survival rate of patients. Several FDA‐approved BRAF inhibitors have been used for treatment of metastatic melanoma, but overall therapeutic efficacy has been limited. Lutetium‐177 (177Lu) enables simultaneous tracking of tracer accumulation with single‐photon emission computed tomography and radiotherapy. Therefore, the codelivery of 177Lu alongside chemotherapeutic agents using nanoparticles (NPs) might improve the therapeutic outcome in metastatic melanoma. Cellulose nanocrystals (CNC NPs) can particularly deliver payloads to lung capillaries in vivo. Herein, 177Lu‐labeled CNC NPs loaded with vemurafenib ([177Lu]Lu‐CNC‐V NPs) is developed and the therapeutic effect in BRAF V600E mutation‐harboring YUMM1.G1 murine model of lung metastatic melanoma is investigated. The [177Lu]Lu‐CNC‐V NPs demonstrate favorable radiolabel stability, drug release profile, cellular uptake, and cell growth inhibition in vitro. In vivo biodistribution reveals significant retention of the [177Lu]Lu‐CNC‐V NPs in the lung, liver, and spleen. Ultimately, the median survival time of animals is doubly increased after treatment with [177Lu]Lu‐CNC‐V NPs compared to control groups. The enhanced therapeutic efficacy of [177Lu]Lu‐CNC‐V NPs in the lung metastatic melanoma animal model provides convincing evidence for the potential of clinical translation for theranostic CNC NP‐based drug delivery systems after intravenous administration. This study describes theranostic cellulose nanocrystals ([177Lu]Lu‐cellulose nanocrystals (CNC)‐V nanoparticles (NPs)) for the codelivery of BRAF inhibitor vemurafenib and the radioisotope lutetium‐177 for chemotherapy and radiotherapy of pulmonary metastases of melanoma through enhanced retention in the lung. The [177Lu]Lu‐CNC‐V NPs prolong the survival of syngeneic YUMM1.G1 melanoma tumor‐bearing mice and decrease the tumor burden in the lung over either vemurafenib or radiotherapy alone.